A Proposal to Mitigate Energy Consumption through the Sustainable Design Process in Tunis - Achour-Younsi, Safa; Chabchoub, Athar; Jouini, Nour El Houda; Kharrat, Fakher (Journal of Contemporary Urban Affairs, 2022)
The main objective of this paper is to assess the energy efficiency of residential buildings in Tunis. To this end, three complementary studies were carried out at different levels. Initially, a diagnosis of the building’s adaptability to climate change at urban and architectural scales was established. The methodology adopted was based on indicators obtained following a cross-reference of environmental assessment tools. This made it possible to highlight the lacunary factors related to thermal comfort. According to this finding, the second research was set up to focus on outdoor thermal comfort. The methodology adopted is based on numerical simulations and calculations of comfort indices. The results demonstrated the importance of specific morphological indicators at the urban scale. Finally, the third research is interested in the architectural scale to assess the building’s thermal comfort and energy consumption. It was performed through numerical simulations. The results demonstrated the impact of specific physical indicators on buildings’ thermal comfort and energy behavior. Ultimately, this research highlighted the gap factors in urban and architectural design in Tunis. It detected the most significant physical and morphological indicators to be considered for sustainable urban design.